El uso de los juegos de roles como estrategia didáctica en la expresión oral en estudiantes de sexto año de Educación General Básica de la Escuela Alejandro Sergio Bermeo, cantón Chimbo, provincia de Bolívar, período lectivo 2024-2025. - Simaliza Tariz, Segundo Manuel (2025)
The purpose of this research was to analyze and understand the impact of role-playing as a teaching tool on the development of oral expression among sixth-grade students of Basic General Education at Alejandro Sergio Bermeo School, located in the Chimbo canton, Bolívar province, during the 2024-2025 school year. The study was conducted using a qualitative approach, which helped to fully understand the students' needs and difficulties in oral communication. To achieve the specific objectives, an initial assessment of oral expression was conducted, teaching strategies focused on the use of role-playing were identified, and finally, a teaching guide was created tailored to the educational context. Through observation and in-depth analysis, it was evident that role-playing contributes to the development of verbal fluency, confidence in public speaking, and class participation. The results confirm that this tool not only improves oral expression but also motivates students, encourages interaction, and strengthens essential communication skills. It concludes by stating that the use of role-playing represents an effective and meaningful educational strategy, and its immediate implementation in the classroom is recommended.